Bone mineralization density and femoral neck fragility. - Loveridge, N; Power, J; Reeve, J; Boyde, A (2004)
The traditional view of osteoporotic fractures is that they result from a reduction in bone mass combined with alterations in the micro-architecture. Apart from the effects of bone remodeling, the material properties of the remaining bone are thought to be unaffected. To test this, we compared the degree of matrix mineralization in femoral neck biopsies taken from cases of intracapsular hip fracture with age- and sex-matched postmortem controls. Whole femoral neck biopsies from seven female hip fracture cases (72-90 years) and nine controls (68-94 years) were embedded in methylmethacrylate, and sections stained with Solochrome Cyanin R for analysis of osteoid. The blocks were then diamond micro-milled, carbon coated, and analyzed for the degree of matrix mineralization using halogenated dimethacrylate standards for quantitative backscattered electron (qBSE) imaging (20 kV, entire block face, sampling interval 5 microm). The BSE gray scale was adjusted such that 0 corresponds to an electron backscattering coefficient of 0.1159 (approximately 1.70 g/ml) and 255-0.1519 (approximately 2.18 g/ml). Remodeling and mineralization data were analyzed for both the whole biopsy face and on a regional (anterior; inferior, posterior, or superior) basis. Over the whole biopsy, the level of mineralization was lower in the cases than the postmortem controls (-2.8%, P < 0.05). In both cases and controls, cortical mineralization was higher in the inferior (compressive) region compared with superior (tensile) region (P < 0.05). Mineralization was lower in all regions of the cases (inferior: -3.3%; posterior: -3.1%; anterior: -2.7%; superior: -1.6%) compared to the controls. Mineralization density in cancellous bone was not regionally dependent but was lower in the fracture cases (-3.5%; P = 0.001). Although there were weak relationships between osteoid formation (%O.Ar/B.Ar) and the mean level of mineralization in both cortical (P = 0.068) and cancellous (P < 0.01) bone, adjustment for this did not markedly affect the case-control differences. In conclusion, this study has shown that in cases of intracapsular hip fracture, matrix mineralization is reduced in the femoral neck. Unexpectedly, in view of the likely role of mild to moderate vitamin D deficiency osteopathy in hip fracture, this decreased mineralization was independent of osteoid indices and therefore potentially independent of bone age. This raises the possibility that alterations in the bone matrix such as excessive glycation or changes in the composition of the collagen fibrils affect its mineralization in hip fracture cases.